For Whom the Bell Tolls: A Story of War for the Cause of Humanity and Democracy - K.C, Chandra Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2021)
Set against the backdrop of Spanish Civil War (1936-1939), For Whom the Bell Tolls provides the firsthand account of that war which Hemingway experienced by serving as a war correspondent. In the novel he takes the side of the Republic for the cause of humanity and democracy. The protagonist Robert Jordan, an American professor from Montana, volunteers his services in the war for anti-fascist cause. He himself thinks that he is inherently antifascist republican, who believes in life, liberty and pursuit of happiness. The novel asserts that the activities shown by the fascists or nationalists were full of selfish and misdirected aggressive impulses. This paper claims that the protagonist and other characters voluntarily involve in the war for the cause of humanity and democracy. The protagonist voluntarily takes part in blowing up the bridge at Guadarrama Mountains near Segovia to stop the Fascists away from the mountains to make the Republican attack successful. He was convinced that the Republicans meant for democratic, civilian, secular order. So he takes part in the war in foreign land for the cause of humanity. This war is related to politics, and the novel is in favour of republican alliance. The novel shows that war is inevitable part for the Republicans for their humanitarian cause. The novel tries to justify the war for the sake of preservation of republican norms like humanity, democracy, freedom, equality, rights of people and brotherhood.